Ketidaksantunan Berbahasa Mahasiswa dalam Proses Perkuliahan (Studi pada Program Studi Tadris Bahasa Indonesia UIN Fatmawati Sukarno Bengkulu) - Randi, Randi; Sari, Wenny Aulia (ESTETIK : Jurnal Bahasa Indonesia, 2023)
This study aims to describe the form of impoliteness in student language in the lecture process. The study was conducted on students of the Indonesian Language Tadris Departement at Fatmawati Sukarno Bengkulu State Islamic University (UIN). The data analysis method used is descriptive-qualitative. This study found violations or impoliteness in: 1) maxims of wisdom in 3 utterances; 2) modesty maxim of 4 utterances; 3) sympathy maxim of 2 utterances; 4) the maxim of appreciation is 4 utterances; 5) the maxim of agreement is 1 utterance; 6) the maxim of agreement is not found. This research concludes that the impoliteness in the language of Indonesian Tadris Departement students at UIN Fatmawati Sukarno is found in the maxims of impoliteness, tact, humility, sympathy, appreciation, and agreement